Changes in brain structure and function following chronic exposure to inhaled vaporised cannabis during periadolescence in female and male mice: A multimodal MRI study. (21st March 2022) - Coleman, James R.; Madularu, Dan; Ortiz, Richard J.; Athanassiou, Maria; Knudsen, Alexa; Alkislar, Ilayda; Cai, Xuezhu; Kulkarni, Praveen P.; Cushing, Bruce S.; Ferris, Craig F.
Abstract: Background and Aims: Social norms and legality surrounding the use of medical and recreational cannabis are changing rapidly. The prevalence of cannabis use in adolescence is increasing. The aim of this study was to assess any sex‐based neurobiological effects of chronically inhaled, vaporised cannabis on adolescent female and male mice. Methods: Female and male mice were exposed daily to vaporised cannabis (10.3% Δ‐9‐tetrahydrocannabinol [THC] and 0.05% cannabidiol [CBD]) or placebo from postnatal day 23 to day 51. Following cessation of treatment, mice were examined for changes in brain structure and function using noninvasive multimodal magnetic resonance imaging (MRI). Data from voxel‐based morphometry, diffusion weighted imaging and rest state functional connectivity were registered to and analysed with a 3D mouse atlas with 139 brain areas. Following imaging, mice were tested for their preference for a novel object. Results: The effects were sexually dimorphic with females showing a unique distribution and inverse correlation between measures of fractional anisotropy and apparent diffusion coefficient localised to the forebrain and hindbrain. In contrast males displayed significant increased functional coupling with the thalamus, hypothalamus and brainstem reticular activating system as compared with controls. Cannabis males also presented with altered hippocampal coupling and deficits in cognitive function. Conclusion: Chronic exposure to inhaled vaporised cannabis had significant effects on brain structure and function in early adulthood corroborating much of the literature. Females presented with changes in grey matter microarchitecture, while males showed altered functional connectivity in hippocampal circuitry and deficits in object recognition. Abstract : Sex difference in response to chronic exposure to inhaled cannabis throughout periadolescence. Females present with a reorganisation of the gray matter microarchitecture, while males show enhanced function connectivity to brainstem reticular activating system.